2022
DOI: 10.3354/meps14081
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and reproduction of the heterotrophic dinoflagellate Noctiluca scintillans in Jiaozhou Bay, China

Abstract: Outbreaks of the heterotrophic dinoflagellate Noctiluca scintillans have impacted the Chinese coastal ecosystem for decades; however, which and how environmental factors affect its reproductive pattern and further influence its population dynamics remain to be investigated. From January 2019 to January 2020, 9 cruises were conducted at 12 stations in Jiaozhou Bay, China. The different life stages of N. scintillans were distinguished and quantified with the assistance of microscopic observation and quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Generally speaking, the spatial distribution may be related to regional environmental characteristics including temperature, salinity, topography, hydrologic conditions, and nutrients. Researches had shown that suitable hydrologic conditions are beneficial to the rapid increase in the local cell density of N. scintillans (Fevre & Grall, 1970; Huang & Qi, 1997; Zhang et al, 2022). Among Chinese coastal provinces, Guangdong and Fujian have the longer coastline, numerous islands, and bays, which can reduce the disturbance of strong currents and winds and provide favorable conditions for the occurrence of N. scintillans blooms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, the spatial distribution may be related to regional environmental characteristics including temperature, salinity, topography, hydrologic conditions, and nutrients. Researches had shown that suitable hydrologic conditions are beneficial to the rapid increase in the local cell density of N. scintillans (Fevre & Grall, 1970; Huang & Qi, 1997; Zhang et al, 2022). Among Chinese coastal provinces, Guangdong and Fujian have the longer coastline, numerous islands, and bays, which can reduce the disturbance of strong currents and winds and provide favorable conditions for the occurrence of N. scintillans blooms.…”
Section: Discussionmentioning
confidence: 99%
“…Researches had shown that suitable hydrologic conditions are beneficial to the rapid increase in the local cell density of N. scintillans (Fevre & Grall, 1970;Zhang et al, 2022). Among Generally, HABs are usually driven by several factors, nutrients (or foods) are only the material basis, but not the decisive factor (Wang, Wu, et al, 2020).…”
Section: Reasons For the Centralized Occurrence Of N Scintillans Bloo...mentioning
confidence: 99%
“…In addition to its role in the regulation of carbon transfer within marine food webs, N. scintillans also serves as a crucial factor for nutrient regeneration [13,24]. This organism can accumulate and regenerate substantial quantities of dissolved nutrients (e.g., NH 4 + and PO 4 3− ) and organic substances [23,25,26].…”
Section: Introductionmentioning
confidence: 99%